Analysis of Nexus among Socioeconomic Status, Happiness, Gratitude, and Psychological Wellbeing in Adults - Abbas, Salbia; Tariq, Mariam; Amin, Zainab; Ijaz, Syeda Muqadas (Pakistan Journal of Humanities and Social Sciences, 2024)
Pakistan's population faces heightened susceptibility to mental health disorders and overall psychological well-being concerns due to the country's myriad social and economic challenges. The present research explored the relationships among adults' socioeconomic status, gratitude, happiness, and psychological well-being. Utilizing a cross-sectional study design and quantitative research methodology, a sample of 350 adults was selected through purposive sampling techniques. The study utilized a self-developed demographic sheet in conjunction with standardized questionnaires, including the Subjective Happiness Scale (SHS) and the Ryff Scale of Psychological Well-Being (PWB). The SHS, comprising four self-report items, was crafted by psychologist Carol D. Ryff. Conversely, the PWB, a 42-item scale, was designed to gauge six dimensions of well-being and happiness: autonomy, environmental mastery, personal growth, positive relationships with others, meaning in life, and self-acceptance. Additionally, the Gratitude Questionnaire-20, developed by Bernabe Valero and Jose Salvador Blasco Magraner, was employed. The study underscores a positive nexus between socioeconomic status, gratitude, happiness, and psychological well-being. Methodologically, it employs a Pearson product-moment correlation for descriptive statistics and multiple linear regressions to forecast the relationship between psychological well-being and happiness, gratitude, and socioeconomic status (SES). Results illuminate a robust direct correlation among gratitude, happiness, SES, and psychological well-being, with all variables exhibiting strong positive associations. Notably, happiness and SES demonstrate a significant Pearson Product Moment Correlation (r=0.135*, p=0.032), underscoring their pivotal role. Furthermore, linear regression analysis, while controlling for GRT, SH, and SES, unveils the substantial predictive capacity of happiness and gratitude on adults' psychological well-being, elucidated by an R-squared value of 0.15. Collectively, these findings accentuate the salient influence of socioeconomic status, happiness, and gratitude on psychological well-being, fostering a deeper comprehension of their interconnectedness.